2014
DOI: 10.1093/aob/mcu192
|View full text |Cite
|
Sign up to set email alerts
|

Fruit removal increases root-zone respiration in cucumber

Abstract: Background and AimsMany attempts have been made to avoid the commonly observed fluctuations in fruit initiation and fruit growth in crop plants, particularly in cucumber (Cucumis sativus). Weak sinks of the fruit have been assumed to result in low sink/source ratios for carbohydrates, which may inhibit photosynthesis. This study focuses on the effects of low sink–source ratios on photosynthesis and respiration, and in particular root-zone respiration.MethodsMature fruit-bearing cucumber plants were grown in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The clear enhancement of root‐zone CO 2 respiration as a result of fruit removal confirms earlier results from hydroponic systems obtained by Kläring et al (). The authors demonstrated that the estimated accumulated contributions of the root's energy requirements for maintenance, growth, and nutrient uptake (i.e., total autotrophic root respiration) contributed less than 50% to the observed effect, leaving the other half for heterotrophic respiration of root exudates and dead root cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The clear enhancement of root‐zone CO 2 respiration as a result of fruit removal confirms earlier results from hydroponic systems obtained by Kläring et al (). The authors demonstrated that the estimated accumulated contributions of the root's energy requirements for maintenance, growth, and nutrient uptake (i.e., total autotrophic root respiration) contributed less than 50% to the observed effect, leaving the other half for heterotrophic respiration of root exudates and dead root cells.…”
Section: Discussionsupporting
confidence: 90%
“…To investigate the effect of actual root exudation on root‐zone N 2 O emissions, while excluding alternative causes, we manipulated the C source:sink ratio to increase plant root exudation. We followed the procedure that was used by Kläring, Hauschild, and Heißner (), who showed that removal of all fruits at once during vegetative growth stage in cucumber plants drastically enhances root zone carbon dioxide (CO 2 ) emissions as a result of increased exudation of C substrates, at least within a few days after sink removal. The experiment was performed under realistic growing conditions in a greenhouse specifically designed to continuously measure the gas exchange in the root zone.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of the higher dry matter content in leaves, stems, and fruits of the constant low temperature relative to the variable temperatures was most probably the restriction in the formation of new leaves and stem sections and the lower extension rate of the fruits. A significant increase in dry matter content of leaves, stems, and fruits due to a lack of sinks for assimilates caused by fruit removal was also observed by Marcelis (1994b) and Kl€ aring et al (2014). Heißner and Drews (1986) showed that cucumber plants grow well at night heating set points of 11°C and produce, with some delay, the same yield compared with plants cultivated at night heating set points of 17°C.…”
Section: Discussionmentioning
confidence: 59%
“…This indicates that any growth inhibition in the long term due root size limitations is not to be expected. A tremendous increase in root growth was also reported when sinks in the form of fruit were removed from the plants (Kl€ aring et al, 2014;Marcelis, 1994b). Therefore, sink limitations in the shoot are likely the cause of the larger root size for plants at constant temperatures compared with those at variable temperatures.…”
Section: Discussionmentioning
confidence: 78%
“…This is another hurdle for PMFCs growing food plants as most of them are valued for their fruits. However, there are also indications that the translocation of carbon compounds to the roots is enhanced upon removal of carbon sinks in the plant, i.e., removal of the fruits (Kläring, Hauschild, & Heißner, 2014). Hence, such fluctuations in voltage of PMFCs growing food plants are expected and mainly attributed to its development stage and presence of carbon sinks.…”
Section: Individual Performance Of Pmfcsmentioning
confidence: 99%